#### Question

Find and correct the errors in the statement: (3*x* + 2)^{2} = 3*x*^{2} + 6*x* + 4

#### Solution

L.H.S. = (3*x *+ 2)^{2} = (3*x*)^{2} + 2(3*x*)(2) + (2)^{2} [(*a* + *b*)^{2} = *a*^{2} + 2*ab* + *b*^{2}]

= 9*x*^{2} + 12*x* + 4 ≠ R.H.S

The correct statement is (3*x* + 2)^{2} = 9*x*^{2} + 12*x* + 4

Is there an error in this question or solution?

Advertisement

Advertisement

Find and Correct the Errors in the Statement: (3x + 2)Square2 = 3xsquare2 + 6x + 4 Concept: Concept of Find the Error.

Advertisement